The battle for neutrality: The Listening Service of the Dutch Government in Exile During the Second World War. Issue 4 (2nd October 2019) - Kuitenbrouwer, Vincent
Abstract : Following the German invasion of the Netherlands in May 1940, a Dutch government in exile was set up in London. One of the most important activities of these exiles was to make propaganda against the Nazi's and throughout the war they operated Radio Oranje (Radio Orange), a wireless station that broadcasted to the Netherlands using BBC-transmitters. Another part of the Dutch broadcasting outfit in England was a 'listening service' that made daily reports about Dutch-language radio broadcasts from Hilversum by the Nazi regime. This article draws from a complete, and previously unused, set of these monitoring reports to analyse the Dutch propaganda war in the ether. The source material reveals that notions of Dutch neutrality were central to the radio broadcasts at both sides of the North Sea. In addition, the reports show how the London broadcasters singled out and targeted specific Nazi propagandists whom they thought to be the most dangerous.